A Holistic Approach to Competence Building - Maharashtra Experiment - Jha, Arvind Kumar (Indian Forester, 1998)
Appropriate competence building has no alternative for a profession like forestry in India. Due emphasis on this aspect for all levels including support staff is an essential precondition for strengthening both professionalism as well as image of the Forest Department as a public service in our country.